Harmonizing Sustainability Disclosure and Financial Performance. An In-depth Exploration within the European Energy Industry and Beyond - MITITEAN, Pompei; SĂRMAȘ, Florina-Nicoleta (Management Dynamics in the Knowledge Economy, 2023)
This study seeks to investigate how the sustainability disclosure influence the financial performance of companies listed in the Top 100 Global Energy Leaders. The Refinitiv Eikon database in the main source where the data was collected for the 2017-2021 period, resulting in a data set of 361 observations for 71 companies. The analysis examined global and regional variables, and the results obtained using the SPSS statistical package were found to be mixed. The findings revealed that the ESG score had a significant negative impact on both Return on Equity (ROE) and Return on Assets (ROA) for the overall sample and Asia. In contrast, the impact was negative but statistically insignificant for Europe and positive but insignificant for North America. Furthermore, the environmental score had a negatively impact on ROA for the overall sample, while its influence was statistically insignificant in Asia, Europe and North America for both ROA and ROE. Additionally, the social score demonstrated a significant negative impact on the overall sample and Asia, while its impact was not significant in other regions. In terms of governance score, it significantly negatively affected ROE for the overall sample, Asia, and Europe, but had a positive and significant impact in North America. This existing literature in the field is completed in new results from the companies acting in the energy sector in different regions of the world. These findings have also some practical implications, being valuable for stakeholders in the decision-making process and for team management who seek to incorporate sustainable practises into corporate strategies.